The Guided Inquiry Learning Model Aided by Audiovisual Media Improves Students' Mathematics Learning Outcomes - Prasanti, Ni Putu; Suarjana, I Made; Wira Bayu, Gede (Universitas Pendidikan Ganesha, 2023)
The low student mathematics learning outcomes are due to the teacher's lack of ability to apply appropriate learning models and media in teaching and learning activities. This research aims to discover the differences in mathematics learning outcomes between the experimental class group by applying the guided inquiry learning model assisted by audiovisual media and the control class group, which applies the conventional learning model in third-grade elementary school. This research belongs to the type of quasi-experimental research. The population in this study were all third-grade elementary school students, totaling 97 students. Sampling in this study was carried out using random sampling techniques or random sampling. The number of samples in this study was 60 third-grade elementary school students. Data collection uses a learning achievement test as an objective instrument; the test is given individually to determine student learning outcomes. This objective test contains 15 questions with answer choices a, b, and c. The research data were then analyzed using descriptive analysis techniques, which included the mean, mode, median, and standard deviation using IMB SPSS Software 25. The results of the data analysis showed that there was an influence of the assisted guided inquiry learning model. Audiovisual media on the mathematics learning outcomes of third-grade elementary school students. It was concluded that the guided inquiry learning model assisted by audiovisual media can improve the learning outcomes of elementary school students.